Distinction between concepts of “structural-functional-parametric model” and “parametric model” of information knowledge objects - Kolybenko, E. N. (Advanced engineering research (Rostov-na-Donu, Russia), 2020)
Introduction. Fundamentally important problems of the structure mapping and transformation, functions and parameters of various properties in the systems of information knowledge objects organization, as well as functionally different parameters in the management processes of transformations of material objects, are considered. For this purpose, structural-functional-parametric models and parametric models are respectively used. The distinction between these concepts is relevant and practically significant. The scientific novelty of the presented work involves studying methods and information tools used to determine functionally different technological schemes for the interaction of objects at the stages of design and pre-processing engineering.Materials and Methods. The concept of a “structural-functional-parametric model” is associated with the definition of the structure of the basic knowledge objects of the subject area. In this case, the “linking base” is the methods and corresponding means of system engineering in the infological modeling technology that are used to solve practical problems. The concept of a “parametric model” is associated with the solution to practical problems of the process control. Nature of these tasks is functionally different (technical, physical, chemical, biological). It should also be clarified that, in this case, we are talking about converting the parameters of various properties of real objects by methods and means of system engineering (almost a mathematical apparatus).Results. A “structural-functional-parametric model” and a “parametric model” are general theoretical concepts that have invariant properties necessary for solving practical problems of the subject knowledge area. Considering the organization system and management processes in this way, note that it is required to maintain data and logical connections be-tween them under static and dynamic settings.Discussion and Conclusions. To solve practical problems in the subject knowledge area according to the technology of information logical modeling, certain methods, tools, algorithms, and operations are used. The most complete mapping and transformation of information objects is possible only in structural-functional-parametric models and databases of their solutions. The application of structural-functional-parametric models is the most important condition for a success-ful transition to a high-level deterministic automation of information technology for solving practical problems of the subject area. As an example of such a problem, we can cite the machining production design engineering.